2013
DOI: 10.1111/jnc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of leptin signaling in Alzheimer disease: evidence for neuronal leptin resistance

Abstract: Leptin signaling has received considerable attention in the Alzheimer disease (AD) field. Within the past decade, the peptide hormone has been demonstrated to attenuate tau hyperphosphorylation in neuronal cells and to be modulated by amyloid-β. Moreover, a role in neuroprotection and neurogenesis within the hippocampus has been shown in animal models. To further characterize the association between leptin signaling and vulnerable regions in AD, we assessed the profile of leptin and the leptin receptor in AD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 46 publications
3
111
0
Order By: Relevance
“…If so, since leptin plays a key role in the developing brain (Steppan and Swick, 1999;Stieg et al, 2015;Farr et al, 2014;Bouret, 2010;Johnston et al, 2014;Pérez-González et al, 2011;Busch et al, 2011;Folch et al, 2012;Zhang et al, 2013;Mancini et al, 2014;Davis et al, 2014) are the high leptin concentrations in serum associated with high CSF leptin and low leptin receptors mRNA in target areas like hippocampus as in Alzheimer's patients? (Bonda et al, 2014a(Bonda et al, , 2014b. If indeed, aberrant leptin signaling is present in urban children as in patients with neuroinflammatory entities, i.e., AIDS and Alzheimer's disease (Bonda et al, 2014a(Bonda et al, , 2014bHuang et al, 2007;Johnston et al, 2014) will children's brain development be compromised?…”
Section: Discussionmentioning
confidence: 99%
“…If so, since leptin plays a key role in the developing brain (Steppan and Swick, 1999;Stieg et al, 2015;Farr et al, 2014;Bouret, 2010;Johnston et al, 2014;Pérez-González et al, 2011;Busch et al, 2011;Folch et al, 2012;Zhang et al, 2013;Mancini et al, 2014;Davis et al, 2014) are the high leptin concentrations in serum associated with high CSF leptin and low leptin receptors mRNA in target areas like hippocampus as in Alzheimer's patients? (Bonda et al, 2014a(Bonda et al, , 2014b. If indeed, aberrant leptin signaling is present in urban children as in patients with neuroinflammatory entities, i.e., AIDS and Alzheimer's disease (Bonda et al, 2014a(Bonda et al, , 2014bHuang et al, 2007;Johnston et al, 2014) will children's brain development be compromised?…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite peripheral hyperproduction of leptin in obese individuals, brain resistance to its action will also develop. Bonda et al (2014) demonstrated recently that besides up-regulation of leptin in AD patients' CSF and hippocampus, leptin receptor mRNA was decreased in the brain tissue and its protein was localized to neurofibrillary tangles. Interestingly, leptin CSF levels showed a positive relation with the Braak staging (plaque and tangle distribution at different stages of Alzheimer's disease progression) and were independent of age and BMI.…”
Section: Leptinmentioning
confidence: 97%
“…Accumulation of amyloid beta (A ) and tau hyperphosphorylation within the CNS are implicated significantly in the pathogenesis of neurodegenerative diseases like AD and PD [30][31][32], and leptin affects these two vital processes [33]. Dysregulation of leptin signaling pathway and neuronal leptin resistance have been recently shown to underlie the pathophysiology of AD [33].…”
Section: Aberrant Leptin Signaling In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Dysregulation of leptin signaling pathway and neuronal leptin resistance have been recently shown to underlie the pathophysiology of AD [33]. Ob-Rb trafficking to the cell membrane depends on proper functioning of microtubules, and tau protein is a microtubule associated protein [34,35].…”
Section: Aberrant Leptin Signaling In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation